Acid‐Labile Thermoresponsive Copolymers That Combine Fast pH‐Triggered Hydrolysis and High Stability under Neutral Conditions. Issue 37 (24th July 2015) - Zhang, Qilu; Hou, Zhanyao; Louage, Benoit; Zhou, Dingying; Vanparijs, Nane; De Geest, Bruno G.; Hoogenboom, Richard
Abstract Biodegradable polymeric materials are intensively used in biomedical applications. Of particular interest for drug‐delivery applications are polymers that are stable at pH 7.4, that is, in the blood stream, but rapidly hydrolyze under acidic conditions, such as those encountered in the endo/lysosome or the tumor microenvironment. However, an increase in the acidic‐degradation rate of acid‐labile groups goes hand in hand with higher instability of the polymer at pH 7.4 or during storage, thus posing an intrinsic limitation on fast degradation under acidic conditions. Herein, we report that a combination of acid‐labile dimethyldioxolane side chains and hydroxyethyl side chains leads to acid‐degradable thermoresponsive polymers that are quickly hydrolyzed under slightly acidic conditions but stable at pH 7.4 or during storage. We ascribe these properties to high hydration of the hydroxy‐containing collapsed polymer globules in conjunction with autocatalytic acceleration of the hydrolysis reactions by the hydroxy groups.